2005
DOI: 10.1161/01.str.0000169903.09253.c7
|View full text |Cite
|
Sign up to set email alerts
|

Induced Spreading Depression Activates Persistent Neurogenesis in the Subventricular Zone, Generating Cells With Markers for Divided and Early Committed Neurons in the Caudate Putamen and Cortex

Abstract: Background and Purpose-Status epilepticus and cerebral ischemia stimulate persistent neurogenesis in the adult brain, but both conditions cause neuronal damage. We determined whether spreading depression, a common epiphenomenon of these conditions, stimulates persistent neurogenesis. Methods-We analyzed the effect of KCl-induced spreading depression on persistent neurogenesis and the spatio-temporal distribution of cells exhibiting immunohistochemical markers for divided and early committed neurons (new neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 32 publications
2
47
0
Order By: Relevance
“…Although progenitor cells migrating from the SVZ (subventricular zone) were also a candidate for newborn astrocytes in the cerebral cortex. However, the BrdU-labeled cell density in the SVZ was not affected by SD induction (Yanamoto et al, 2005). This finding suggests that origin of the newborn cells in the cortex was unlikely to be progenitor cells in the SVZ.…”
Section: Discussionmentioning
confidence: 77%
“…Although progenitor cells migrating from the SVZ (subventricular zone) were also a candidate for newborn astrocytes in the cerebral cortex. However, the BrdU-labeled cell density in the SVZ was not affected by SD induction (Yanamoto et al, 2005). This finding suggests that origin of the newborn cells in the cortex was unlikely to be progenitor cells in the SVZ.…”
Section: Discussionmentioning
confidence: 77%
“…Spreading depolarizations have many adverse effects and it has been clearly shown in animals that they facilitate death when they invade metabolically compromised tissue [16,52,53,55], but they may also have beneficial effects in the surrounding healthy tissue where they may precondition, or promote plasticity or regeneration [121][122][123]. Unfortunately, it is more difficult to block spreading depolarization in more metabolically compromised tissue, and not vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Previously, we found that induced multiple SD waves in the adult rat brain under normal condition activates cell division of neural progenitor cells in the subventricular zone (SVZ), enhancing persistent neurogenesis toward the olfactory bulb. 6 Furthermore, induced SD generates new immature neurons, at an ectopic location, in cortical Layers V to VI. 6 Recently, it was found that induced SD activates neurogenesis in the hippocampal subgranular zone.…”
mentioning
confidence: 99%